Contaminación ambiental del agua por el uso indebido de pesticidas agrícolas en plantaciones de banano en el Ecuador - Suarez Murillo, Ángel David (2020)
The objective of the present work to be studied is the environmental contamination of water due to the improper use of pesticides used in banana plantations. In banana plantations for the control of pests and diseases, pesticides are used can be beneficial for the control of pests such as herbs and insects, but they do not realize that these chemicals pollute groundwater poisoning all living beings and including beings. humans who consume these waters, so they are prone to diseases. When applying pesticides, avoid harm to organisms that are not the target of the application. Therefore, it is important to avoid water contamination and pesticide drift. Some pesticides can harm the natural enemies of crop pests, thus causing outbreaks of secondary pests. The possibility of choosing pesticides with the least effect on natural enemies is considered. For the development of the research, it will be carried out in a bibliographic manner in which information will be obtained through magazines, books, scientific articles, web pages, manual newspapers, etc; in which the different information will be compiled to prepare the project. Based on the above, it was determined that the use of pesticides with excessive use is a constant danger to the health of the inhabitants who live around the banana plantations. The waters, as well as the surface and underground waters, are those that receive the residues of chemical products and circulate to all the communities near the banana plantations.